Binder, negative pole piece and battery

By using water-soluble highly imidized polyimide binder, the bond failure problem caused by volume expansion during charging and discharging of lithium-ion battery negative electrode materials is solved, and the stability and battery life of the battery negative electrode are improved. .

CN119463795AActive Publication Date: 2025-02-18SHENZHEN HAODYNE TECH CO LTD

Patent Information

Application Number
CN202510025343.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-02-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries have severe volume expansion during charging and discharging, resulting in binder failure, electrode material shedding and rapid attenuation of battery performance.

Method used

Using polyimide-based binders with water-soluble and high imidation degree, the ion conduction and bonding properties of the binder are improved by introducing sulfonate salts, so that they can be fully mixed with the negative electrode slurry and tightly Bonded electrode material.

Benefits of technology

It improves the integrity and stability of the negative electrode of the battery, extends the service life of the battery, and maintains battery efficiency and stable power output during repeated charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a binder, a negative pole piece and a battery, the binder comprises a polyimide binding material, the polyimide binding material comprises a first structural unit from an amino sulfonic acid monomer, a second structural unit from an amino monomer, and a third structural unit from an anhydride monomer; the mass percentage content of sulfonate radicals in the polyimide binding material is 15-35 wt%. The binder provided by the invention has a good binding effect, and is beneficial to improving the stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a binder, a negative electrode sheet and a battery. Background Art

[0002] Lithium batteries are widely used in various fields due to their high energy density and long life. At present, the negative electrode material of lithium-ion batteries is mainly graphite, which is widely used as the negative electrode of lithium-ion batteries because of its stable structure, small volume expansion, high conductivity and good cycle stability. However, its low theoretical capacity (372mAh / g) limits its application in high-capacity battery systems. Compared with graphite materials, silicon-based materials have higher mass specific capacity (4200 mAh / g) and are one of the most promising negative electrode materials for next-generation lithium-ion batteries. However, silicon-based negative electrode materials have severe volume expansion (>300%) during the charging and discharging process, so there is a possibility of crushing and pulverization of electrode material particles during the charging process, resulting in separation between the silicon material and the substrate, causing rapid decay of battery capacity and poor cycle performance.

[0003] Due to the poor mechanical properties of traditional binders, it is difficult to adapt to the significant volume expansion of high-silicon negative electrodes during the charge and discharge process. Although polyimide binders have good mechanical properties, they usually need to be dissolved in polar solvents such as N-methylpyrrolidone. The existing negative electrode slurry is usually aqueous in consideration of environmental protection and slurry processability. Therefore, polyimide binders dissolved in polar solvents are difficult to fully mix with aqueous negative electrode slurries, which greatly affects their bonding effect. Water-soluble polyimide binders can solve the above problems well. Common water-soluble polyimide binders are usually stored in the form of their precursor polyamic acid salts. The use process requires high-temperature imidization treatment of polyamic acid salts, which increases equipment costs. In addition, in order to match the coating line speed, the high-temperature imidization process lasts for a short time, and the degree of imidization of polyamic acid salts is limited, resulting in poor bonding performance when used as a binder.

[0004] Therefore, there is an urgent need for an adhesive that is water-soluble, has a high degree of imidization, and has good bonding properties. Summary of the invention

[0005] The present invention provides a binder which is water-soluble and can be fully mixed with the components of the negative electrode slurry in the battery preparation process, has a good binding effect, and is beneficial to improving the battery stability.

[0006] The present invention provides a negative electrode plate, which is prepared using the above-mentioned binder. The binder tightly combines the active material particles in the negative electrode plate with the conductive agent and the current collector, and can also maintain the integrity of the electrode material during repeated charging and discharging, reducing the risk of active material falling off.

[0007] The present invention provides a battery, comprising the above-mentioned negative electrode plate, the battery can maintain its battery efficiency during repeated charging and discharging, and can provide stable power output.

[0008] The first aspect of the present invention provides an adhesive, which includes a polyimide adhesive material, wherein the polyimide adhesive material includes: a first structural unit derived from an aminosulfonic acid monomer, a second structural unit derived from an amino monomer, and a third structural unit derived from an anhydride monomer;

[0009] The mass percentage of sulfonate groups in the polyimide-based adhesive material is 15-35 wt %.

[0010] The binder as described above, wherein the molar ratio of the first structural unit to the second structural unit is (4-9): (6-1); and / or,

[0011] The molar ratio of the sum of the first structural unit and the second structural unit to the third structural unit is (0.95-1.10):1.

[0012] The adhesive as described above, wherein the weight average molecular weight of the polyimide-based adhesive material is 30,000-400,000 g / mol.

[0013] The adhesive as described above, wherein the adhesive further comprises an alkaline solution that dissolves the monovalent cations of the polyimide-based adhesive material;

[0014] And / or, the molar ratio of the monovalent cation from the base in the binder to the sulfonate group in the polyimide-based binder is (0.8-1.05):1.

[0015] The binder as described above, wherein the aminosulfonic acid monomer comprises a diamine compound containing a sulfonic acid group; and / or,

[0016] The amino monomer includes at least one of an aromatic diamine compound, an aminosilane compound, a dimeramine compound, and a polyetheramine compound.

[0017] In the binder as described above, the aminosulfonic acid monomer includes at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 2,2'-benzidine disulfonic acid, 2,5-diaminobenzene-1,4-disulfonic acid, and 4,4'-diaminostilbene-2,2'-disulfonic acid.

[0018] The adhesive as described above, wherein the amino monomer includes at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, ethylene glycol bis(2-aminophenyl) ether, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, diamine, and polyetheramine.

[0019] The binder as described above, wherein the anhydride monomer includes at least one of pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 4,4'-(4,4'-isopropyldiphenoxy)bis(phthalic anhydride), butanetetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride.

[0020] A second aspect of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active layer, and the negative electrode active layer comprises the binder as described above.

[0021] A third aspect of the present invention provides a battery, wherein the battery comprises the negative electrode plate as described above.

[0022] The binder provided by the present invention can be fully mixed with the negative electrode slurry components in the battery preparation process by using a water-soluble polyimide binder material, and the components are tightly bonded together, which is beneficial to maintaining the integrity of the battery negative electrode and improving the stability of the battery. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In the preparation process of lithium batteries, in order to increase the theoretical capacity of the battery, silicon-based materials are often used as the active material of the negative electrode battery. However, compared with conventional graphite negative electrode materials, silicon-based negative electrode active materials are more likely to expand in volume during the charge and discharge process, causing the binder to fail and silicon particles to fall off in all directions, accelerating the collapse of the electrode structure and ultimately causing rapid decay of battery performance.

[0025] The reason why the above-mentioned binders have limited bonding effects may be that most binders are often dissolved in organic solvents when used, and it is difficult for the organic solvent to fully contact with the negative electrode material components dissolved in water, thus resulting in limited bonding effects.

[0026] Therefore, a water-soluble binder is needed that can fully contact with the negative electrode material components dissolved in water, improve the bonding effect between the components and improve the stability of the battery.

[0027] Based on this, the first aspect of the present invention provides an adhesive, including a polyimide adhesive material, the polyimide adhesive material including: a first structural unit derived from an aminosulfonic acid monomer, a second structural unit derived from an amine monomer, and a third structural unit derived from an anhydride monomer;

[0028] The mass percentage of sulfonate groups in the polyimide adhesive material is 10-35wt%.

[0029] Specifically, the present invention introduces sulfonate salts into polyimide to obtain a polyimide-based adhesive material, so that the adhesive has good water solubility and ion conductivity. The inventor speculates that the reason may be that the sulfonate group is highly polar, which makes it show good solubility in water or other polar solvents. In addition, the sulfonate structure, as a strong polar group, can interact with lithium ions in the lithium-ion battery environment, providing a channel for ion transmission, which is beneficial to the transmission of lithium ions during the operation of the lithium battery.

[0030] The polyimide adhesive material of the present invention is composed of a first structural unit derived from an aminosulfonic acid monomer, a second structural unit derived from an amine monomer, and a third structural unit derived from an anhydride monomer. Among them, the second structural unit derived from the amine monomer provides a soft segment structure for the polyimide adhesive material, and the first structural unit derived from the aminosulfonic acid monomer and the third structural unit derived from the anhydride monomer provide a hard segment structure. The structure of the combination of the soft and hard segments enables the polyimide adhesive material to have a higher elastic modulus and elongation at break. Furthermore, the adhesive comprising the polyimide adhesive material can better maintain its shape and reduce deformation when subjected to external force, thereby improving the mechanical strength of the overall structure of the battery. In addition, the structure of the combination of the soft and hard segments also enables the polyimide adhesive material to have a higher elongation at break, which enables the polyimide adhesive material to undergo reversible deformation in a larger range without breaking, showing excellent toughness. This helps the binder, including polyimide-based binder materials, absorb and disperse stress when the electrode material undergoes volume changes (such as expansion and contraction during charge and discharge cycles), prevent crack propagation, ensure that the electrode maintains stable performance during long-term use, maintain the integrity of the electrode's internal structure, reduce the risk of active material shedding, and thereby extend the battery's service life.

[0031] In addition, in order to balance the solubility, bonding and ion conductivity of the binder, the present invention further limits the mass percentage of sulfonate groups in the polyimide-based binder to 15-35wt%. For example, the mass percentage of sulfonate groups in the polyimide-based binder includes but is not limited to 15wt%, 20wt%, 25wt%, 30wt%, 35wt% or any two thereof.

[0032] Specifically, the mass percentage of the sulfonate groups in the polyimide-based adhesive material can be calculated by testing using a nuclear magnetic resonance hydrogen spectrum method.

[0033] The present invention forms a polyimide-based adhesive material by using a first structural unit derived from an aminosulfonic acid monomer, a second structural unit derived from an amine monomer, and a third structural unit derived from an anhydride monomer, and further controls the mass percentage of sulfonate groups in the polyimide-based adhesive material to be 10-35wt%, so that the adhesive has good bonding effect and ion transmission effect in a lithium-ion battery, and gives the adhesive a higher elastic modulus and elongation at break.

[0034] In the polyimide adhesive material, the molar ratio of the first structural unit to the second structural unit is (4-9): (6:1). For example, the molar ratio of the first structural unit to the second structural unit includes but is not limited to 4:6, 5:5, 6:4, 7:3, 8:2, 9:1 or a range consisting of any two thereof.

[0035] In another specific embodiment, the molar ratio of the total molar sum of the first structural unit and the second structural unit to the second structural unit is (0.95~1.05):1. For example, the molar ratio of the first structural unit to the second structural unit includes but is not limited to 0.95:1, 0.97:1, 1:1, 1.03:1, 1.05:1 or a range consisting of any two of them.

[0036] The molar ratio of the first structural unit to the second structural unit and the molar ratio of the third structural unit to the second structural unit in the above-mentioned polyimide-based adhesive material can be analyzed by nuclear magnetic resonance spectroscopy. Specifically, the polyimide-based adhesive material is fully dissolved in deuterated water, a 30-60 mg / mL polymer aqueous solution is prepared, and the polyimide-based adhesive material is measured by 1H NMR using a nuclear magnetic resonance spectrometer, and the composition of each unit structure in the polyimide-based adhesive material is calculated based on the chemical shift value and the integrated area.

[0037] The present invention can control the molar ratio of the soft segment and the hard segment in the polyimide-based adhesive material by controlling the molar ratio of the first structural unit to the second structural unit and the molar ratio of the third structural unit to the second structural unit, which is beneficial to further improve the elastic modulus and elongation at break of the polyimide-based adhesive material.

[0038] In addition, the inventors found that the weight average molecular weight of the polyimide adhesive material will also affect its bonding performance. Therefore, the present invention further limits the weight average molecular weight of the polyimide adhesive material to 30000~400000 g / mol. For example, the weight average molecular weight of the polyimide adhesive material includes but is not limited to 30000 g / mol, 100000 g / mol, 200000 g / mol, 400000 g / mol or a range consisting of any two of them. When the weight average molecular weight of the polyimide adhesive material is within the above range, the polyimide adhesive material has a good hardness, which can make the adhesive have a higher mechanical strength.

[0039] As mentioned above, the polyimide adhesive material is a condensate formed by condensing aminosulfonic acid monomers, amine monomers, and anhydride monomers. In detail, the aminosulfonic acid monomers and the amino monomers provide amino groups to condense with the anhydride monomers. Among them, the condensate formed by the amino monomer after participating in the condensation provides a soft segment structure, and the condensate formed by the aminosulfonic acid monomers and the anhydride monomers after participating in the condensation provides a hard segment structure. The structure of the combination of soft and hard segments makes the polyimide adhesive material have a higher elastic modulus and elongation at break, which can make the polyimide adhesive material have good mechanical properties and toughness, which is beneficial for the adhesive including the polyimide adhesive material to maintain good stability and bonding performance in lithium batteries.

[0040] It should be clear that the polyimide adhesive material can be stored in either solid form or liquid form. When the polyimide adhesive material is stored in solid form, the solid is pure polyimide adhesive material, and at this time, the sulfonic acid group structure in the polyimide adhesive material is in the form of sulfonic acid; when the polyimide adhesive material is stored in liquid form, the solid of the polyimide adhesive material is dissolved in alkaline solution for storage, and at this time, the sulfonic acid group in the polyimide adhesive material exists in the form of sulfonate. The present invention does not specifically limit the type of alkali in the alkaline solution, as long as it can dissolve the limited imide adhesive material. For example, the alkali is selected from at least one of potassium hydroxide, sodium hydroxide, and triethylamine.

[0041] The adhesive provided by the present invention is in liquid form when used, that is, the adhesive of the present invention also includes an alkali solution that dissolves the monovalent cations of the polyimide adhesive material. At this time, the sulfonic acid group in the polyimide adhesive material exists in the form of sulfonate. Through the action of the alkali solution, the sulfonic acid in the polyimide adhesive material forms a sulfonate with the alkali in the alkali solution, so that the polyimide adhesive material can be completely dissolved in water, which greatly improves the water solubility of the adhesive.

[0042] In another specific embodiment, in order to further improve the water solubility of the binder, the present invention further controls the molar ratio of the monovalent cations from the alkali in the alkali solution to the sulfonate in the polyimide-based binder to be (0.80-1.10):1. For example, the molar ratio of the monovalent cations from the alkali in the alkali solution to the sulfonate in the polyimide-based binder includes but is not limited to 0.80:1, 0.90:1, 1.00:1, 1.10:1 or a range consisting of any two of them.

[0043] In the above-mentioned binder, the aminosulfonic acid monomer includes a diamine compound containing a sulfonic acid group.

[0044] In another specific embodiment, the amine monomer includes at least one of an aromatic diamine compound, an aminosilane compound, a dimeramine compound, and a polyetheramine compound.

[0045] The above-mentioned aminosulfonic acid monomers and amine monomers can undergo efficient condensation reactions with anhydride monomers, respectively providing hard segment structures and soft segment structures for the polyimide adhesive materials generated after the condensation reaction, which is beneficial to improving the elastic modulus and elongation at break of the polyimide adhesive materials, and further beneficial to improving the bonding properties of the adhesive.

[0046] Furthermore, the aminosulfonic acid monomer includes at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 2,2'-benzidine disulfonic acid, 2,5-diaminobenzene-1,4-disulfonic acid, and 4,4'-diaminobenzene-2,2'-disulfonic acid. The above aminosulfonic acid monomer can provide a hard segment structure for the polyimide adhesive material, which is beneficial to improve the mechanical strength of the polyimide adhesive material.

[0047] As mentioned above, the amino monomer includes at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, ethylene glycol bis(2-aminophenyl) ether, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, diamine, and polyetheramine. For example, diamine includes at least one of ethylenediamine, hexamethylenediamine, phenylenediamine, isophoronediamine, diethylenetriamine, and triethylenetetramine, and polyetheramine includes at least one of aminoethylaminopropyl-terminated polyethylene glycol (PEG) and bis[3-(aminomethyl)oxypropyl]amine. The above compounds have good flexibility and can provide a soft segment structure for the polyimide adhesive material in the present invention, which is beneficial to improve the elongation at break of the adhesive.

[0048] In addition, the anhydride monomers include at least one of pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride, 4,4'-(4,4'-isopropyldiphenyloxy)bis(phthalic anhydride), butane tetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride. The above anhydride monomers can also provide a hard segment structure for the polyimide adhesive material, thereby facilitating the mechanical strength of the polyimide adhesive material.

[0049] The binder of the present invention is obtained by the following preparation method, comprising the following steps:

[0050] A polyimide adhesive material is obtained by condensing an aminosulfonic acid amino monomer, an amine monomer and an anhydride monomer;

[0051] The polyimide adhesive material is dissolved in an alkali solution to obtain the adhesive.

[0052] The present invention can prepare a water-soluble adhesive by using the above method. It should be clear that in the above preparation method, the polyimide adhesive material prepared after the condensation reaction can be stored as a solid, and the solid can be dissolved in an alkaline solution when used; or the polyimide adhesive material can be dissolved in an alkaline solution to obtain a finished adhesive and stored.

[0053] Furthermore, in the preparation method of the above-mentioned adhesive, the preparation process of the polyimide adhesive material includes:

[0054] 1) dissolving aminosulfonic acid monomer and amino monomer in a solvent to obtain a mixed solution;

[0055] 2) adding anhydride monomers to the mixed solution for condensation reaction to obtain a mixed system containing condensation products;

[0056] 3) After adding a water-carrying agent to the mixed system, dehydration treatment is performed under reflux to obtain a condensation product;

[0057] The condensation product is mixed with a poor solvent and then subjected to precipitation treatment to obtain a polyimide-based adhesive material.

[0058] In step 1), the present invention does not specifically limit the type of solvent, as long as the aminosulfonic acid monomer and the amino monomer can be dissolved. For example, the solvent includes at least one of dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and m-cresol. The present invention does not specifically limit the dissolution method, as long as the aminosulfonic acid monomer and the amino monomer can be completely dissolved in the solvent. For example, the aminosulfonic acid monomer and the amino monomer can be added to the solvent and stirred so that the above two solutes can be evenly distributed in the solvent.

[0059] In step 2), the present invention adds anhydride monomers to the mixed solution to carry out a condensation reaction. In the condensation reaction, the aminosulfonic acid monomer and the amino monomer each provide an amino group to react with the anhydride monomer to form a condensate to obtain a mixed system containing the condensation product.

[0060] In the above condensation reaction, water will be generated in the mixed system containing the condensate. In step 3), the present invention can remove the condensation product in the mixed system by adding a water-carrying agent to the above mixed system. The present invention does not specifically limit the amount of the water-carrying agent used, which can be determined according to actual conditions. It should be clear that the water-carrying agent can promptly bring the by-product water generated in the thermal imidization process of the condensation product out of the system, promote the right shift of the reaction, and the obtained condensation product has a high degree of imidization. Therefore, the additional step of thermal imidization of the polyimide adhesive required in conventional industry is omitted, which is beneficial to saving industrial costs and improving industrial economy.

[0061] Then, the condensation product is mixed with a poor solvent and then precipitated to obtain a polyimide adhesive material. The present invention does not specifically limit the type of the poor solvent, as long as it does not react with the condensation product and can precipitate the condensation product. For example, the poor solvent includes at least one of ethanol, isopropanol, n-hexane, cyclohexane, dichloromethane, acetone, and tetrahydrofuran.

[0062] The present invention does not limit the amount of the poor solvent, which can be selected according to actual conditions. It can be understood that before the above precipitation treatment, the condensation product is cooled to avoid the influence of temperature on the poor solvent; after the above precipitation treatment, the precipitate obtained by the precipitation treatment is washed and dried to obtain a dry polyimide adhesive material.

[0063] The present invention does not specifically limit the reagent and treatment temperature of the washing treatment and the treatment time and treatment temperature of the drying treatment, as long as a dry polyimide adhesive material can be obtained. For example, the cooled condensation product can be precipitated and washed in an ethanol solution at room temperature, and then dried in a vacuum drying oven at 60-120° C. for 6-24 hours to obtain a dry polyimide adhesive material.

[0064] Specifically, in the mixed solution, the molar ratio of the aminosulfonic acid monomer to the amino monomer is (4-9): (6-1). For example, the molar ratio of the aminosulfonic acid monomer to the amino monomer includes but is not limited to 4:6, 5:5, 7:3, 8:2, 9:1 or a range consisting of any two of them. By further limiting the molar ratio of the aminosulfonic acid monomer to the amino monomer, a polyimide adhesive material having a suitable soft segment and hard segment composition can be obtained.

[0065] In another specific embodiment, in step 2), the molar ratio of the total molar amount of aminosulfonic acid monomers and amine monomers to the molar amount of anhydride monomers is 1:(0.95-1.05). For example, the molar ratio of the total molar amount of aminosulfonic acid monomers and amine monomers to the molar amount of anhydride monomers includes but is not limited to 1:0.95, 1:1, 1:1.05 or any two thereof. The present invention can effectively control the occurrence of condensation reaction by limiting the molar ratio of the total molar amount of aminosulfonic acid monomers and amine monomers to the molar amount of anhydride monomers, and prepare a polyimide adhesive material having a weight average molecular weight of 30,000-400,000 g / mol and having a suitable soft segment and hard segment composition.

[0066] In another specific embodiment, the reaction temperature of the condensation reaction is 0-60°C, and the reaction time is 6-24h. For example, the reaction temperature of the condensation reaction includes but is not limited to 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C or a range consisting of any two thereof; the reaction time of the condensation reaction includes but is not limited to 6h, 10h, 14h, 18h, 20h, 24h or a range consisting of any two thereof. The present invention is conducive to the generation of a polyimide adhesive material with a suitable molecular weight by controlling the reaction temperature and reaction time of the condensation reaction, which is conducive to improving the bonding performance of the adhesive.

[0067] Based on the consideration of the effectiveness of the thermal imidization treatment, in another specific embodiment, the thermal imidization treatment temperature is 140-200°C, and the treatment time is 2-8h. For example, the treatment temperature of the thermal imidization treatment includes but is not limited to 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or a range consisting of any two thereof; the reaction time of the condensation reaction includes but is not limited to 2h, 4h, 6h, 8h or a range consisting of any two thereof. The present invention controls the treatment temperature and treatment time of the thermal imidization treatment within the above range, which is conducive to the effective thermal imidization treatment of the condensation product, and obtains a polyimide adhesive material with a higher degree of imidization, which is conducive to improving the bonding performance of the adhesive.

[0068] In another specific embodiment, the water-carrying agent in the above preparation method includes at least one of toluene, xylene, and cyclohexane. By using the above water-carrying agent, an azeotropic mixture can be effectively formed with the by-product water of the thermal imidization process, thereby reducing the boiling point of water in the system, making it easier for the condensation by-product water to be distilled out of the reaction system, thereby promoting the forward progress of the thermal imidization reaction.

[0069] The second aspect of the present invention provides a negative electrode sheet, which includes a negative electrode active layer, and the negative electrode active layer includes the above-mentioned binder or the binder prepared by the above-mentioned binder preparation method. In the negative electrode active layer, each component is tightly bonded together by the binder, and its integrity can still be maintained during the battery charging and discharging process, which is conducive to improving the cycle stability and life of the battery.

[0070] The third aspect of the present invention provides a battery, including the negative electrode plate provided by the third aspect of the present invention, and the battery can maintain its high efficiency performance during repeated charge and discharge processes to ensure stable and reliable power output.

[0071] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0072] Example 1

[0073] The preparation method of the binder of this embodiment comprises the following steps:

[0074] 1) Add 2,5-diaminobenzene-1,4-disulfonic acid (134.1 g, 0.5 mol) and ethylene glycol bis(2-aminophenyl) ether (122.2 g, 0.5 mol) into NMP (4071.6 g), and stir until dissolved to obtain a mixed solution.

[0075] 2) Cyclobutanetetracarboxylic dianhydride (196.1 g, 1.0 mol) was added three times with an interval of 2 hours each time, and the reaction was carried out at 25°C for 24 hours to obtain a mixed system containing a condensation product.

[0076] 3) After adding 407 g of toluene water-carrying agent to the above-mentioned mixed system, the mixture was stirred evenly, heated to 180°C, and refluxed to remove water for 8 hours; after cooling, the product was precipitated in ethanol, washed, and vacuum dried at 100°C for 6 hours to obtain a dry polyimide adhesive material;

[0077] Among them, the mass percentage of sulfonate in the polyimide adhesive material is 19 wt%;

[0078] In the polyimide adhesive material, the molar ratio of the first structural unit derived from the aminosulfonic acid monomer to the second structural unit derived from the amino monomer is 1:1;

[0079] The molar ratio of the total molar amount of the first structural unit derived from the aminosulfonic acid monomer and the second structural unit derived from the amino monomer to the third structural unit derived from the anhydride monomer is 5:5;

[0080] The molar ratio of the monovalent cation from the base to the sulfonate group in the polyimide adhesive material is 1:1;

[0081] The weight average molecular weight of the polyimide-based adhesive material is 286,000 g / mol.

[0082] 4) Potassium hydroxide (112.2 g, 2 mol; the molar ratio of lithium ions to sulfonate groups is 1:1) is dissolved in 4248 g of water to prepare alkaline water, and the dried polyimide adhesive material is added to the alkaline water, and stirred continuously until dissolved to obtain an adhesive.

[0083] Example 2

[0084] This embodiment is basically the same as Embodiment 1, except that:

[0085] In step 1), 2,5-diaminobenzene-1,4-disulfonic acid (187.7 g, 0.7 mol) and ethylene glycol bis(2-aminophenyl) ether (73.3 g, 0.3 mol) were added to NMP (4071.6 g), and stirred until dissolved to obtain a mixed solution.

[0086] In step 2), cyclobutanetetracarboxylic dianhydride (196.1 g, 1.0 mol) was added three times with an interval of 2 hours each time, and the condensation reaction was carried out at 25° C. for 24 hours to obtain a mixed system containing a condensation product.

[0087] The mass percentage of sulfonate groups in the polyimide adhesive material of this embodiment is 27 wt %;

[0088] In the polyimide adhesive material, the molar ratio of the first structural unit derived from the aminosulfonic acid monomer to the second structural unit derived from the amino monomer is 7:3;

[0089] The molar ratio of the total molar amount of the first structural unit derived from the aminosulfonic acid monomer and the second structural unit derived from the amino monomer to the third structural unit derived from the anhydride monomer is 1:1;

[0090] The weight average molecular weight of the polyimide-based adhesive material is 227,000 g / mol.

[0091] Example 3

[0092] This embodiment is basically the same as Embodiment 1, except that:

[0093] In step 1), 2,5-diaminobenzene-1,4-disulfonic acid (241.4 g, 0.8 mol) and ethylene glycol bis(2-aminophenyl) ether (24.4 g, 0.2 mol) were added to NMP (4071.6 g), and stirred until dissolved to obtain a mixed solution.

[0094] In step 2), cyclobutanetetracarboxylic dianhydride (196.1 g, 1 mol) was added three times with an interval of 2 hours each time, and the condensation reaction was carried out at 25° C. for 24 hours to obtain a mixed system containing a condensation product.

[0095] The molar ratio of the first structural unit to the second structural unit in the polyimide adhesive material prepared in this embodiment is 8:2;

[0096] The molar ratio of the total molar amount of the first structural unit derived from the aminosulfonic acid monomer and the second structural unit derived from the amino monomer to the third structural unit derived from the anhydride monomer is 1:1;

[0097] The mass percentage of sulfonate groups in the polyimide adhesive material of this embodiment is 30.4 wt %;

[0098] The weight average molecular weight of the polyimide-based adhesive material is 185,000 g / mol.

[0099] Example 4

[0100] This embodiment is basically the same as Embodiment 1, except that:

[0101] In step 1), 2,5-diaminobenzene-1,4-disulfonic acid (160.9 g, 0.6 mol) and ethylene glycol bis(2-aminophenyl) ether (97.7 g, 0.4 mol) were added to NMP (4071.6 g), and stirred until dissolved to obtain a mixed solution.

[0102] In step 2), cyclobutanetetracarboxylic dianhydride (196.1 g, 1 mol) was added three times with an interval of 2 hours each time, and the condensation reaction was carried out at 25°C for 24 hours to obtain a mixed system containing a condensation product.

[0103] The molar ratio of the first structural unit to the second structural unit in the polyimide adhesive material prepared in this embodiment is 6:4;

[0104] The molar ratio of the total molar amount of the first structural unit derived from the aminosulfonic acid monomer and the second structural unit derived from the amino monomer to the third structural unit derived from the anhydride monomer is 1:1;

[0105] The mass percentage of sulfonate groups in the polyimide adhesive material of this embodiment is 23.4 wt %;

[0106] The weight average molecular weight of the polyimide-based adhesive material is 248,000 g / mol.

[0107] Example 5

[0108] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the molar ratio of the monovalent cation from the base to the sulfonate group in the polyimide-based adhesive material is 1.2:1.

[0109] Example 6

[0110] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the molar ratio of the total molar sum of the first structural unit derived from the aminosulfonic acid monomer and the second structural unit derived from the amino monomer to the third structural unit derived from the anhydride monomer is 0.95:1; the weight average molecular weight of the polyimide-based adhesive material is 35,000 g / mol; and the molar ratio of the monovalent cation from the base to the sulfonate group in the polyimide-based adhesive material is 1:1.

[0111] Example 7

[0112] This embodiment is substantially the same as embodiment 1, except that the aminosulfonic acid monomer used in this embodiment is 2,2'-benzidine disulfonic acid and the amino monomer is 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, and the anhydride monomer used is 4,4'-biphenyl ether dianhydride;

[0113] In the polyimide adhesive material, the molar ratio of the first structural unit derived from the aminosulfonic acid monomer to the second structural unit derived from the amino monomer is 7:3;

[0114] The molar ratio of the total molar sum of the first structural unit from the aminosulfonic acid monomer and the second structural unit from the amino monomer to the third structural unit from the anhydride monomer is 1:1;

[0115] The mass percentage of sulfonate in the polyimide adhesive material prepared in this embodiment is 19.2 wt %;

[0116] The molar ratio of the monovalent cation from the base to the sulfonate group in the polyimide adhesive material is 1:1;

[0117] The weight average molecular weight of the polyimide-based adhesive material is 364,000 g / mol.

[0118] Comparative Example 1

[0119] This comparative example is basically the same as Example 1, except that:

[0120] In step 1), 2,5-diaminobenzene-1,4-disulfonic acid (40.2 g, 0.15 mol) and ethylene glycol bis(2-aminophenyl) ether (207.7 g, 0.85 mol) were added to NMP (4071.6 g), and stirred until dissolved to obtain a mixed solution.

[0121] In step 2), cyclobutanetetracarboxylic dianhydride (196.1 g, 1 mol) was added three times with an interval of 2 hours each time, and the condensation reaction was carried out at 25°C for 24 hours to obtain a mixed system containing a condensation product.

[0122] In the polyimide adhesive material prepared in this comparative example, the molar ratio of the first structural unit derived from the aminosulfonic acid monomer to the second structural unit derived from the amino monomer is 1.5:8.5;

[0123] The molar ratio of the total molar amount of the first structural unit derived from the aminosulfonic acid monomer and the second structural unit derived from the amino monomer to the third structural unit derived from the anhydride monomer is 1:1;

[0124] The weight average molecular weight of the polyimide-based adhesive material is 248,000 g / mol.

[0125] The mass percentage of sulfonate groups in the polyimide-based adhesive material in this comparative example is 5.9%.

[0126] The molar ratio of the monovalent cation from the base to the sulfonate group in the polyimide adhesive material is 1:1;

[0127] The polymer is insoluble in aqueous alkaline solutions.

[0128] Comparative Example 2

[0129] This comparative example is substantially the same as Example 1, except that, in the polyimide adhesive material, the molar ratio of the first structural unit derived from the aminosulfonic acid monomer to the second structural unit derived from the amino monomer is 10:0;

[0130] The molar ratio of the total molar sum of the first structural unit from the aminosulfonic acid monomer and the second structural unit from the amino monomer to the third structural unit from the anhydride monomer is 1:1;

[0131] The mass percentage of sulfonate in the polyimide adhesive material prepared in this embodiment is 37.8 wt %;

[0132] The number average molecular weight of the polyimide-based adhesive material is 293,000 g / mol.

[0133] Test example:

[0134] Preparation of positive electrode sheet: 96.80wt% of nickel cobalt lithium manganese oxide ternary material, 1.5wt% of conductive agent Super. P, 0.5wt% of conductive graphite KS-6, 1.20wt% of binder polyvinylidene fluoride and N-methylpyrrolidone are mixed to prepare positive electrode slurry, and then the positive electrode slurry is coated on the surface of aluminum foil, and the positive electrode sheet is obtained after drying and rolling;

[0135] Preparation of negative electrode sheet: 1.5wt% of the above-provided binder, 0.5wt% of thickener sodium carboxymethyl cellulose, 1wt% of conductive agent Super. P, 1wt% of styrene-butadiene rubber, 5.0wt% of silicon-carbon active negative electrode, 92.0wt% of graphite and deionized water are mixed to prepare a negative electrode slurry, and then the negative electrode slurry is coated on the surface of copper foil, and the negative electrode sheet is obtained after drying and rolling;

[0136] Preparation of the electrolyte: In a glove box filled with argon, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate were mixed in a mass ratio of 3:2:5, lithium hexafluorophosphate was added, and the mixture was stirred evenly to obtain the electrolyte for the lithium ion battery.

[0137] Preparation of lithium-ion battery: Assemble the above-mentioned positive electrode sheet, negative electrode sheet, electrolyte and separator to obtain a lithium-ion battery.

[0138] Mechanical properties test of adhesive:

[0139] The adhesives in Examples 1-7 and Comparative Example 2 were cast into a dumbbell-shaped mold with a length of 100 mm, a width of 10 mm, and a thickness of 0.5 mm. After being placed at room temperature for 48 hours, the molds were demoulded and trimmed, and then baked in an oven at 85°C for 4 hours to obtain an adhesive film. The mechanical properties were tested using an electronic universal testing machine. At room temperature, the lower fixture was kept stationary, and the upper fixture was stretched upward at a stretching rate of 5 mm / min. The elastic modulus and elongation at break measured in the elastic deformation section were recorded. The test results are shown in Table 1.

[0140] Capacity retention test:

[0141] The capacity retention rate of each battery was tested. The specific test method was as follows: at 25°C, the battery was charged to 4.50V at a constant current of 1C, then charged to 4.50V at a constant voltage of 0.05C, and then discharged to 3.0V at a discharge rate of 1C. This charge and discharge cycle was repeated 500 times, and the discharge capacity at the first cycle and the discharge capacity at the 500th cycle were measured. The capacity retention rate Q after 500 cycles was calculated according to the following formula:

[0142] Capacity retention rate Q = Q 200 / Q1*100%, see Table 1 for specific test results.

[0143] Table 1

[0144]

[0145] “-” means no measurement is required.

[0146] It can be seen from the table that when the binder prepared in Example 1-7 is used in a battery relative to that in Comparative Example 1-2, the negative electrode plate can have higher conductivity, elastic modulus, cycle stability and elongation at break, so that the battery has better stability and longer life.

[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A binder, characterized in that: The polyimide adhesive material includes: a first structural unit derived from an aminosulfonic acid monomer, a second structural unit derived from an amino monomer, and a third structural unit derived from an anhydride monomer; The mass percentage of sulfonate groups in the polyimide-based adhesive material is 15-35 wt %.

2. The adhesive according to claim 1, characterized in that The molar ratio of the first structural unit to the second structural unit is (4-9): (6-1); and / or, The molar ratio of the sum of the first structural unit and the second structural unit to the third structural unit is (0.95-1.10):

1.

3. The adhesive according to claim 1 or 2, characterized in that: The weight average molecular weight of the polyimide adhesive material is 30,000-400,000 g / mol.

4. The adhesive according to claim 1 or 2, characterized in that: The adhesive further comprises an alkaline solution that dissolves the monovalent cations of the polyimide-based adhesive material; And / or, the molar ratio of the monovalent cation from the base in the binder to the sulfonate group in the polyimide-based binder is (0.8-1.05):

1.

5. The adhesive according to claim 1 or 2, characterized in that: The aminosulfonic acid monomer includes a diamine compound containing a sulfonic acid group; and / or, The amino monomer includes at least one of an aromatic diamine compound, an aminosilane compound, a dimeramine compound, and a polyetheramine compound.

6. The adhesive according to claim 1 or 2, characterized in that: The aminosulfonic acid monomer includes at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 2,2'-benzidine disulfonic acid, 2,5-diaminobenzene-1,4-disulfonic acid, and 4,4'-diaminostilbene-2,2'-disulfonic acid.

7. The adhesive according to claim 1 or 2, characterized in that: The amino monomer includes at least one of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, ethylene glycol bis(2-aminophenyl) ether, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, dimeramine, and polyetheramine.

8. The adhesive according to claim 1 or 2, characterized in that: The anhydride monomer includes at least one of pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-biphenyl ether dianhydride, 4,4'-(4,4'-isopropylidene diphenoxy)bis(phthalic anhydride), butanetetracarboxylic dianhydride, and 3,3',4,4'-diphenyl sulfonetetracarboxylic dianhydride.

9. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode active layer, and the negative electrode active layer comprises the binder according to any one of claims 1 to 8.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Sulfonated polyimide with hydrolysis resistance, and preparation method and application thereof

    CN102746511A

  • Preparation method of polyimide resin emulsion bonder

    CN102746819A

  • Environment-friendly type polyimide-based high temperature-resistant adhesive and preparation method thereof

    CN109233734A

  • Sulfonated polyimide binder, electrode plate and lithium ion battery

    CN111777984A

  • Polyimide sulfinate and preparation method and application thereof

    CN116640305A

Cited By

  • Binder, positive plate and battery

    CN121064783A

  • An adhesive, a positive electrode, and a battery

    CN121064783B

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN121528914A

  • Battery cells and their preparation methods, battery devices, power consumption devices and energy storage devices

    CN121528914B